Correlation between the anti-Müllerian hormone and endovaginal ultrasound in the predictivity of polycystic ovary syndrome at Chracerh - C. C., Noa Ndoua; G., Ayissi Ngah; V., Mve Koh; E., Belinga; J. D., Kemfang; J. M., Kasia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Polycystic ovary syndrome (PCOS) is a heterogeneous syndrome posing diagnostic problems in current practice, because of the cumbersomeness associated with the application of the criteria that define it; giving rise to over or under diagnosis of it. Anti-Müllerian hormone (AMH) is an effective alternative in this case, being a stable, reproducible and non-operator dependent marker to diagnose PCOS due to the link that binds it to the multiple pre-antral follicles in the ovaries of PCOS patients. The aim of this study was to determine the threshold value of AMH required to define PCOS in our African population, by revealing the correlation with antral follicles count (AFC) on endovaginal ultrasound. Methods: We carried out a comparative cross-sectional study, with retrospective data collection in 23 infertile patients diagnosed with PCOS according to the Rotterdam 2003 criteria, and 23 non-PCOS infertile controls having performed the AMH test using the Immunotech technique at CHRACERH. Endovaginal ultrasound (U/S) was performed using a 7.5 mega Hertz (MHz) transvaginal transducer by different qualified operators (radiologists, gynecologists). The comparison of the two independent groups (PCOS and non-PCOS) was performed by the Student t-test; correlations between AMH, age, AFC and ovarian volume obtained by the Pearson test; and the diagnostic power of AMH test in PCOS was evaluated by receiver operating characteristic curves (ROC). Results: AMH was approximately twice as high in PCOS compared to controls (6.09 versus 3.80, P <0.001) and was inversely correlated with age (r = -0.301; P ˂0.05); significantly correlated antral follicle count (R = 0.85, P <0.0001) and ovarian volume (r = 0.625, P <0.0001). ROC analysis revealed that the AMH test was very informative for the diagnosis of PCOS with an area under the curve (AUC) at 0.90 (0.81-0.99; 95% CI); and the threshold value given by the farthest point of the diagonal representing the nil contribution test was 4.40 ng/L, and predicted PCOS with a sensitivity of 96% and a specificity of 70%. Conclusions: AMH is a predictive marker for PCOS. It is highly correlated with AFC and ovarian volume and appears to decrease with age. It offers good diagnostic performance in PCOS, with a threshold value of 4.40 ng/L for a sensitivity of 96% and specificity of 70%.